2021
DOI: 10.1111/cen.14594
|View full text |Cite
|
Sign up to set email alerts
|

SDHC phaeochromocytoma and paraganglioma: A UK‐wide case series

Abstract: Objective Phaeochromocytomas and paragangliomas (PPGL) are rare, but strongly heritable tumours. Variants in succinate dehydrogenase (SDH) subunits are identified in approximately 25% of cases. However, clinical and genetic information of patients with SDHC variants are underreported. Design This retrospective case series collated data from 18 UK Genetics and Endocrinology departments. Patients Both asymptomatic and disease‐affected patients with confirmed SDHC germline variants are included. Measurements Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Moreover, clinically ccRCCs have as outlined above, many similarities to neuroendocrine tumours in general. Furthermore, polycythaemia due to EPO production has been reported together with somatostatinoma, paraganglioma, and phaeochromocytoma [75,76]. We found not only EPO but also NSE expression in virtually all ccRCCs, but both markers, were mostly negative in the other types of renal cell carcinomas [2].…”
Section: Neural Crest Origin Of Erythropoietin-producing Cellsupporting
confidence: 57%
“…Moreover, clinically ccRCCs have as outlined above, many similarities to neuroendocrine tumours in general. Furthermore, polycythaemia due to EPO production has been reported together with somatostatinoma, paraganglioma, and phaeochromocytoma [75,76]. We found not only EPO but also NSE expression in virtually all ccRCCs, but both markers, were mostly negative in the other types of renal cell carcinomas [2].…”
Section: Neural Crest Origin Of Erythropoietin-producing Cellsupporting
confidence: 57%
“…A UK-wide series of SDHC cases demonstrated that 65 per cent presented with head and neck paraganglioma. 1202 Around 20 per cent of head and neck paragangliomas and 30 per cent of phaeochromocytomas were metastatic. As with the other genes, penetrance is difficult to estimate.…”
Section: Geneticsmentioning
confidence: 99%
“…48,49 A case series of patients with SDHC mutations from the United Kingdom revealed SDHC mutations in head and neck paraganglioma, extra-adrenal paraganglioma, and pheochromocytoma. 50 Head and neck paragangliomas associated with SDHC mutations are almost always benign and mostly solitary. 51 A case of catecholamine-producing malignant paraganglioma due to SDHC mutation showed G→T transversion in intron 5 + 1 of SDHC , resulting in exon 5 deletion, reading frameshift, 52 and aberrant splicing.…”
Section: Physiological Functions Of Sdhcmentioning
confidence: 99%